English An Assessment of Indigenous Knowledge of Music Therapy in Nigeria - Charles Onomudo Aluede; Arugha A. Ogisi; Fatelyn I. Okakah (Voices, 2023)
Indigenous knowledge of music as therapy as it is understood in Nigeria has to do with the acquisition of information about the application of music for healing in traditional settings. There is no doubt that the use of music to educate, rehabilitate, and bring about healing in Nigerian indigenous societies is an age-long tradition. A survey of traditional music which was carried out through questionnaire and interview methods allude to the fact that most Nigerian cultures firmly believe in the therapeutic potency of music. From the perspectives of some selected Nigerian traditional communities (Esan, Urhobo, Itsekiri, Igbo, Yoruba, Hausa, Bini, and others) this study, therefore, reveals the various forms of manifestations of music healing traditions in different Nigerian communities. Potent as music may be in healing, if the indigenous must beget the modern, there remains a growing need to examine the indigenous understanding of music therapy. As a major aim of this study, we examined the Nigerian construct of illness; illness causation; and how Nigerian people understand music healing and its associated healing techniques. While this work reveals that music in therapy in Nigerian traditional societies has been in use over the ages, regrettably few incidences have been captured in literature. This suggests that this very important branch of music should be introduced into tertiary institutions as an academic field that should embrace cultural and clinical approaches.